A new treatment for canine B-cell lymphoma based on a recombinant single-domain antibody immunotoxin derived from Pseudomonas aeruginosa exotoxin A - André, Ana S.; Dias, Joana N. R.; Moutinho, Isa; Loureiro, Joana; Leonardo, Ana; Nogueira, Sara; Marimon, Rafaela P.; Bule, Pedro; Correia, Jorge; Malhó, Rui; Gano, Lurdes; Correia, João D. G.; et al. (Frontiers in Veterinary Science, 2025)
Canine lymphoma is one of the most common and aggressive hematopoietic tumors in dogs. Despite recent advances in veterinary cancer treatments, the lack of specificity, side effects, and resistance to conventional chemotherapies has opened an urgent need to develop more targeted and safe therapeutics to address this unmet need in dogs. Thus, in the present study, we aimed to generate a new class of therapeutics based on a recombinant single-domain antibody (sdAb) immunotoxin derived from the PE38 Pseudomonas aeruginosa exotoxin A. For this purpose, we fused the PE38 toxin with the specific C5 sdAb antibody, previously developed by our group for canine B-cell lymphoma. This resulted in a stable and highly specific C5-PE38 immunotoxin against canine B-cell lymphoma. The C5-PE38 immunotoxin revealed a potent cytotoxic activity (EC50 = 9.50 ± 0.04 μg/mL) against CLBL-1 canine B-cell lymphoma cells, while promoting inhibition of protein synthesis and, consequently, cell death. Importantly, in vivo results in a CLBL-1 xenograft mouse model demonstrated specific targeted tumor uptake and strong tumor growth inhibition in C5-PE38 treated mice compared with control vehicle-treated mice. The results obtained provide new data validating immunotoxins and recombinant sdAb-PE38 based scaffolds as a novel and promising anti-cancer therapy for the treatment of dog-related tumors, while contributing to comparative oncology.